Habits and behaviours related to the health in adolescents during their leisure time - Gil-Madrona, Pedro; Prieto-Ayuso, Alejandro; Silva, Sheila Aparecida Dos Santos; Serra-Olivares, Jaime; Aguilar Jurado, Miguel Ángel; Díaz-Suárez, Arturo (Anales de Psicología / Annals of Psychology, 2018)
This research attempts to determine which are the common practices related to the participation in sport and physical activities within the consumption of harmful substances in adolescents. A descriptive, correlational and transversal design was performed. A total of 1,140 subjects participated in the study (Mean age: 18.75 ± 6.35 years old; gender: male 46.7%, female 53.3%), of wich 790 were undergraduates and 350 non-undergraduates from the autonomous community of Castilla-La Mancha (Spain). It was used the Evaluation Questionnaire of the Habits related to the Health (Gil-Madrona, González-Víllora, Pastor-Vicedo, & Fernández-Bustos, 2010). Descriptive analysis revealed that a high percentage of adolescents do not practice sport regularly. The differential analysis showed significant statistical values which relates the sport habit with the tobacco, alcohol and/or drugs consumption. It was concluded that the design and development of programmes which foster physical activity are a need.